Results-Based Climate Finance in Practice : Delivering Climate Finance for Low-Carbon Development - World Bank Group; Frankfurt School of Finance and Management (World Bank, Washington, DC, 2017)
Results-based financing is a well-established financing modality in the health and education sectors but it is still in an early stage of deployment in the area of climate change. This report reviews 74 results-based climate financing (RBCF) programs implemented in developing countries with an objective to: assess the characteristics and overall volume of funding flowing through RBCF programs, describe the various approaches to designing and implementing RBCF programs, and compare practical experiences with applying RBCF with the existing theory and literature. The report finds that RBCF can: facilitate carbon pricing and market building, support host countries' policy processes to achieve their NDCs, and leverage private sector activity and financing. RBCF can thus play a critical role in mobilizing the resources and supporting the policies and actions needed to achieve the objectives of the Paris Agreement.